The psychology of learning and motivation. - Ross, Brian H. (Boston, Mass. : Academic Press, 2010)
The Psychology of Learning and Motivation series publishes empirical and theoretical contributions in cognitive and experimental psychology, ranging from classical and instrumental conditioning to complex learning and problem solving. Each chapter thoughtfully integrates the writings of leading contributors, who present and discuss significant bodies of research relevant to their discipline. Volume 51 includes chapters on such varied topics as emotion and memory interference, electrophysiology, mathematical cognition, and reader participation in narrative. * Volume 51 of the highly regarded Psychology of Learning and Motivation series * An essential reference for researchers and academics in cognitive science * Relevant to both applied concerns and basic research.